2022
DOI: 10.14797/mdcvj.1057
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Pathogenesis, and Diagnosis of Cardiac Sarcoidosis

Abstract: Cardiac sarcoidosis (CS) is a widely underdiagnosed yet clinically significant form of granulomatous myocarditis associated with significant morbidity and mortality. Clinical presentation ranges from silent cardiac involvement detected on imaging to cardiomyopathy or sudden cardiac death. Diagnosis of CS remains challenging due to the lack of sensitivity and specificity of any single diagnostic method, underscoring the importance of elevated clinical suspicion and the use of multimodality imaging to guide diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 81 publications
1
12
1
Order By: Relevance
“…On the other hand, traditional risk factors for incident HF such as hypertension, diabetes, obesity, and CKD are more prevalent among black individuals compared to other race/ethnic groups [19] , [27] . In contrast to previous studies [28] , [29] , our analysis has shown that female patients with sarcoidosis and concomitant HF were less likely to be hospitalized compared to their male counterparts. This is likely related to some evidence suggesting that male sarcoidosis patients tend to have more cardiac manifestations [30] , [31] .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, traditional risk factors for incident HF such as hypertension, diabetes, obesity, and CKD are more prevalent among black individuals compared to other race/ethnic groups [19] , [27] . In contrast to previous studies [28] , [29] , our analysis has shown that female patients with sarcoidosis and concomitant HF were less likely to be hospitalized compared to their male counterparts. This is likely related to some evidence suggesting that male sarcoidosis patients tend to have more cardiac manifestations [30] , [31] .…”
Section: Discussioncontrasting
confidence: 99%
“…Histologic proof of the epithelioid granulomas is part of the definition of sarcoidosis. For the heart involvement, the biopsy of endomyocardial tissue has a high specificity, but sampling errors and variable histology reduce the sensitivity down to 20 to 30% (12). Also, endomyocardial biopsies are usually obtained from the right side of the interventricular septum, while granulomas are typically located in the left ventricle (13).…”
Section: Diagnosis Of Cardiac Sarcoidosismentioning
confidence: 99%
“…The majority of patients with sarcoidosis (90%–95%) have pulmonary and lymph node involvement, but isolated CS can occur. In CS, granulomas typically develop in the myocardium, often with endocardial or epicardial extension ( 9 ). The extent and distribution of these granulomas dictate the clinical manifestations.…”
Section: Pathogenesis Of Cardiac Sarcoidosismentioning
confidence: 99%
“…Active myocardial inflammation can result in ventricular arrhythmias, ventricular dysfunction and sudden cardiac death. Furthermore, in the post-inflammatory phase, patchy fibrosis in the ventricular myocardium can develop, further predisposing to ventricular tachyarrhythmias ( 9 ).…”
Section: Pathogenesis Of Cardiac Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation